KOMUNIKASI LISAN LANGKAH SUKSES MANAJER PENJUALAN - Ardhoyo, TE (Universitas Prof. Dr. Moestopo (Beragama), 2013)
Selling point-means the optimal point which successfully improved product sales through sales promotion. Salespromotionis dynamic, and what is implemented now can change dramatically in many respect sover the nextfewyears. The highly dynamic nature of makinga sales pitch is a key selling tool, which is relevant for the ironandpush market conditions that support the sale. In todays modern economy, sales promotion plays a big role.